2019
DOI: 10.3390/ijms20205153
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis β-Carbonic Anhydrases: Novel Targets for Developing Antituberculosis Drugs

Abstract: The genome of Mycobacterium tuberculosis (Mtb) encodes three β-carbonic anhydrases (CAs, EC 4.2.1.1) that are crucial for the life cycle of the bacterium. The Mtb β-CAs have been cloned and characterized, and the catalytic activities of the enzymes have been studied. The crystal structures of two of the enzymes have been resolved. In vitro inhibition studies have been conducted using different classes of carbonic anhydrase inhibitors (CAIs). In vivo inhibition studies of pathogenic bacteria containing β-CAs sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 70 publications
0
45
0
Order By: Relevance
“…This residue has, however, been observed occasionally coordinating Zn 2+ in EcoCA-γ, resulting in a “closed” conformation. This in turn, resulted in a mechanism similar to the β-CAs in which they switch between “open” and “closed” states [ 42 , 43 ]. This phenomenon was, thus, searched for γ-PhCA and γ-PmCA following MD simulations.…”
Section: Resultsmentioning
confidence: 99%
“…This residue has, however, been observed occasionally coordinating Zn 2+ in EcoCA-γ, resulting in a “closed” conformation. This in turn, resulted in a mechanism similar to the β-CAs in which they switch between “open” and “closed” states [ 42 , 43 ]. This phenomenon was, thus, searched for γ-PhCA and γ-PmCA following MD simulations.…”
Section: Resultsmentioning
confidence: 99%
“… 21 An electron-deficient benzene ring with a thiol produces a Meisenheimer complex that dissociates to generate SO 2 , as shown in Figure 3 . 30 Apart from oxidative stress, carbonic anhydrase inhibitors, 31 dihydropteroate synthase and dihydrofolate reductase inhibition, 32 resistance to the aminoglycoside antibiotic kanamycin A, 33 and an undefined mechanism associated with Wag31 33 , 34 may be responsible for desired inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous pieces of evidence support the involvement of CA activity in the survival, pathogenicity and virulence of several species of human pathogens, such as Helicobacter pylori [ 55 , 56 , 57 ], Vibrio cholerae [ 58 ], Brucella suis [ 52 , 59 , 60 , 61 ], Salmonella enterica [ 62 ] and Pseudomonas aeruginosa [ 63 ]. For example, ethoxzolamide ( EZA) was demonstrated to inhibit the V. cholerae virulence in vivo by blocking the cholera toxin gene expression, induced by the bicarbonate produced by the Vibrio CA activity [ 58 ]; this inhibitor can also prejudice the virulence of M. tuberculosis [ 64 ]. Recently, it has been demonstrated that AAZ and some AAZ -based sulfonamides act as potent inhibitors of vancomycin-resistant Enterococcus [ 65 ], which are the leading causes of drug-resistant healthcare-associated infections.…”
Section: Resultsmentioning
confidence: 99%